Effect of zinc in absence and presence of limestone on soybean grown in three different soil types - Moreira, Adônis; Moraes, Larissa A. C.; Bassoli, Paulo G.; Moreira, Pedro A. M. [UNESP]; Nogueira, Thiago A. R. [UNESP] (Taylor & Francis, 2025)
Liming is essential for enhancing economic viability and increasing crop production in acidic soil in tropical and subtropical regions. However, continuous limestone application has been associated with cationic micronutrient deficiency, including zinc (Zn). In an experiment under greenhouse conditions using three soils of different textural classes (Typic Alfisol, Typic Oxisol, and Typic Entisol), we evaluated the growth of soybean after fertilization with limestone and Zn. We applied dolomitic limestone at two rates (equivalent to 0 and 5.0 Mg ha−1) and Zn at four rates (0, 5, 10, and 20 mg kg−1), each with four replicates. These three soil types exhibited distinct nutrient availability. Liming significantly altered soil chemical attributes, particularly causing considerable reduction in Zn availability in Typic Alfisol. Furthermore, liming led to a reduction in Zn concentration in soybean leaves and grains in all the three soil types. Grain yield (GY) increased in the presence of liming, and yield was further enhanced with increasing Zn concentrations. Positive effect was also seen on photosynthetic rate (A), stomatal conductance (gs), and leaf N, Ca, and Zn concentrations, except on P concentration. Even with adequate nutrient concentrations and limestone application, sandy soils had a lower GY.
Keywords: Glycine max; nutritional status; soil chemical attributes; yield components